Selling tourism services at a distance : an analysis of the EU consumer acquis - Bech Serrat, Josep Maria (Springer Berlin Heidelberg, 2012)
New rules on distance selling provided for the Consumer Rights Directive will apply for contracts concluded after 13 June 2014 but not to package holidays or contracts falling within the scope of the Timeshare Directive. Contracts for passenger transport services and contracts for the provision of accommodation, car rental, catering or leisure services if the contract provides for a specific date or period of performance are not covered by some of these rules either. Yet measures aimed at protecting the consumer when a contract is concluded via the phone, the Internet, by mail or other means of distance communication are important to tourism. This book helps readers to navigate through uncertainties in travel contracts regarding information requirements, the right of withdrawal, and providing alternative services. Findings reveal that consumer acquis is not adapted to the features of the tourism industry when an optional instrument based on the Draft Common Frame of Reference might be used in the future.